Emotional Intelligence and Its Relationship with Demographic Variables and Job Satisfaction: A Study Among University-Level Teachers in Nepal - Chapagain, Bal Ram (The International Research Journal of Management Science, 2021)
Given the importance of emotional intelligence (EI) in teaching, this study aims to identify the status of EI of university-level teachers and examine its relationship with various demographic variables and job teachers in Nepal is moderately high. Among the four demographic variables, only the gender, in favour job satisfaction. Since females are found to be more emotionally intelligent than males, strategies to include more females in the faculty pool could be an important step for higher education institutions EI in relation to demographic variables and job satisfaction in Nepalese higher education, and hence this work could be a springboard for more advanced research.